PENDIDIKAN DAN KEHIDUPAN SOSIAL - Puwanto, Nurtanio Agus (Universitas Negeri Yogyakarta, 2007)
Education is it doesn't matter always closely related with social life. That thing is in limited scale earned we to see as interaction of school with public around and education in society itself. In public laymen looks into someone based on it's the social status, like level of it's (the economics social, education even material properties owned).In public is recognized also social institution as an order applied at one particular certain public. Institution of Social is life pattern standard reference a public so that always adhered by group of the public. If some acquitted outside institution embraced a public hence people or the group will be assumed impinges institution which has been specified. Talks about institution of social don't get out of development of culture happened in public.Cultural development hardly influenced by public patterned thinking formed by education obtained, experience of public individual or group of people, foreign intervention and change of internal area and external happened.